(untitled) (ModaPalavra e-periódico, 2022)
In the current production scenario, apparel industries develop products at a fast pace, however, they need to intensify the pursuit of performance excellence to meet the needs of users. Thus, it is necessary to adopt a way of working that incorporates the use of Ergonomics in production processes, after all, it is science that improves the function of clothing, considering harmony and comfort. This article aims to identify studies that have developed resources for the application of Ergonomics in the development of clothing products, through a systematic literature review. 1452 documents were identified, which after filtering, 32 were submitted to bibliometric and content analysis. The results approach Brazil, Portugal, Sweden, China and the United Kingdom, as countries with the largest publications, being mostly models for the pre-development and development phases. In terms of content, the publications focus on: improving the development of functional products; assess comfort and usability; improve protective, sports and professional clothing; and the development of inclusive apparel, haute couture and costumes.